Teacher Perceptions Matter: Psychometric Properties of the Georgia School Personnel Survey of School Climate. Issue 2 (3rd July 2021) - Saint, Jo; Rice, Kenneth G.; Varjas, Kris; Meyers, Joel
Abstract: There are many measures of student perceptions of school climate; accordingly, there is a staggering amount of research examining those perceptions and related outcomes. There is a comparatively small number of measures examining school personnel perceptions. Of those found, only some had evidence of measurement invariance/equivalence (MI/E). None found with evidence of MI/E had evidence of structural invariance/equivalence (SI/E). This article explores these psychometric properties of The Georgia School Personnel Survey (GSPS) of school climate. We analyzed a representative sample of Georgia school personnel ( N  = 166, 887) through exploratory, confirmatory, and multigroup confirmatory factor analysis. Results indicated that the GSPS has a second-order model containing six first-order subscales loading onto a second-order scale (acting as a measure of whole-school climate). Assessment of MI/E and SI/E suggested that the GSPS is an appropriate measure for comparisons based on gender, racial/ethnic identity, grade level, and job classification. Implications for research and practice will be discussed referencing the Cultural–Ecological Model of School Climate (CEMSC). Impact Statement This research provides psychometric properties for the Georgia School Personnel Survey (GSPS) of school climate, giving school personnel, lawmakers, and researchers information necessary to justify the use of the GSPS as a valid tool to assess and confidently compare staff perceptions of school climate. Specifically, this research provides evidence that the GSPS may be used to compare perceptions of school climate between school staff based on demographic characteristics (gender, racial/ethnic identity, job classification, and grade level). This research may be of special interest to a range of stakeholders, including school psychologists, district- and school-level administrators, and policymakers who are interested in comparing perceptions within schools or systems. School psychologists, who are trained as data-based decision-makers, play an important role as advocates to administrators and other school personnel. Specifically, school psychologists can help teams to analyze and interpret data as part of an empirically-based intervention to address the needs of school personnel. Supplemental data for this article is available online at https://doi.org/10.1080/2372966X.2021.1958645 .